From Spreadsheets to Suptech : Technology Solutions for Market Conduct Supervision - World Bank (World Bank, Washington, DC, 2018)
Effective and efficient market conduct supervision is critical to ensuring that financial consumers are protected from unfair business practices and provided with clear and relevant information. Yet market conduct supervision is a challenge in many jurisdictions. Many supervisory authorities are therefore seeking technology-enabled solutions to increase the efficiency and effectiveness of their supervisory activities. This discussion note examines Suptech (that is, supervisory technology) solutions that are being adopted for market conduct supervision, including the implications of these technology solutions for broader supervisory approaches. The note provides a general examination of Suptech, as well as three country case studies that illustrate how Suptech is currently being applied by market conduct supervisory authorities—specifically, in the context of financial consumer protection (using country case studies from the United States and Lithuania) and in the context of AML/CFT (using a country case study from Brazil). The note also highlights cross-cutting considerations, including the risks and challenges that may arise with Suptech.